PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (Survey Pada Konsumen Kelom Geulis Sagitria Collection di Kota Tasikmalaya) - Rafa Nur Afifah; Cece Rakhmat; Barin Barlian (Exchall: Economic Challenge, 2022)
This research intends to identify and analyze the impact of Promotion, Quality of results and Purchase Attention to the Sagitria Collection Group in the City of Tasikmalaya, the Effect of Product Quality on the Purchase Decision of the Sagitria Collection Kelom Geulis in the City of Tasikmalaya simultaneously, The effect of product development and innovation on the Buying Interest of the Column geulis in the city of Tasikmalaya partially. The procedure used in the research is a Quantitative Method. The analysis tool uses multiple linear regression. The data used is primary data. Based on the results of the study, it is known that the influence of product development and quality simultaneously has an important influence on consumer purchasing attention at the Kelom Geulis Sagitria Collection in Tasikmalaya City.